Compact and broadband dual sleeve monopole antenna for GSM, WiMAX and WLAN application. Issue 6 (30th March 2017) - Mohamadzade, B.; Rezaee, A.
ABSTRACT: This paper presents a dual sleeve monopole antenna that covers Global System for Mobile Communications (GSM), worldwide interoperability microwave access (WiMAX), and wireless local area network (WLAN) frequency bands. This new antenna is more wideband and compact structure in compare to other works. Simulation is done by Ansoft HFSS14 and results show the proposed omnidirectional antenna, ranging from 360 MHz to 5.1 GHz that bandwidth is 174% for return loss below −10 dB. The height of structure is 0.16 λ that has been achieved size reduction about 35% in compare to conventional monopole antenna with height 0.25 λ . These characterizations make this antenna very beneficial for jammer application. Jammers make places more secure and comfortable by reducing cell phones disruptions from some public places. The prototype of this structure has been made and the measure results are in good agreement with simulation results. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1271–1277, 2017